Sistem Pendukung Keputusan Pemilihan Kepala Cabang SCO di JNE Menerapkan Kombinasi Metode Dematel dan Aras - Ramadhani, Tri Desy (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2024)
The head of the SCO (Sales Counter Officer) branch is a person who has good experience, knowledge and skills to lead and process finances every day who offer products available from the goods delivery service at the JNE Ekpress company. The SCO branch head also plays a role in organizing and coordinating SCO workers on duty, starting from arranging shifts, taking work records, and minimizing losses caused by SCO input errors. Decision Support Systems are computer-based systems consisting of several components, namely language system components, knowledge system components and problem processing system components, which are interconnected with each other in making a decision. through the use of data and decision models in order to solve a problem. DEMATEL (Decision Making Trial And Evaluation Laboratory) aims to find direct (dependency) in a variable system. The Additive Ratio Assessment (ARAS) method is a method used for ranking criteria. In carrying out the ranking process, this method is very suitable for use in selecting candidates for SCO branch heads. Where the highest value is the best value of the final result. Based on the test results, it is known that Rahmad is a candidate who meets the criteria to become the new SCO branch head with a score of 0.957972 or 96%.